Decrease of CD68 Synovial Macrophages in Celastrol Treated Arthritic Rats - Cascão, Rita (2015)
Rheumatoid arthritis (RA) is a chronic immune-mediated inflammatory disease characterized by cellular infiltration into the joints, hyperproliferation of synovial cells and bone damage. Available treatments for RA only induce remission in around 30% of the patients, have important adverse effects and its use is limited by their high cost. Therefore, compounds that can control arthritis, with an acceptable safety profile and low production costs are still an unmet need. We have shown, in vitro, that celastrol inhibits both IL-1β and TNF, which play an important role in RA, and, in vivo, that celastrol has significant anti-inflammatory properties. Our main goal in this work was to test the effect of celastrol in the number of sublining CD68 macrophages (a biomarker of therapeutic response for novel RA treatments) and on the overall synovial tissue cellularity and joint structure in the adjuvant-induced rat model of arthritis (AIA).